Strategic Strengthening of Citizen Participation and Its Relation to the Decrease in Common Crime at the District Level - Toledo Palomino, ANGEL ARMANDO (2020)
According to INEI (2018), the district of Santiago de Surco is in the eleventh place of incidence of common crime, which causes dissatisfaction of the surcana community towards the public policies applied by the district authorities. Pinochet (2017) indicates that to counter this problem, it is necessary to apply mechanisms aimed at reducing citizen insecurity, with citizen participation being a fundamental tool; For this reason, the study carried out focused on describing the relationship between strategic strengthening and the reduction of common crime. The research focus was quantitative and correlational in scope; Furthermore, the design was non-experimental. The population was made up of the 273,115 inhabitants of the Santiago de Surco district, and 384 randomly selected people were taken as the optimal sample. In addition, the observation technique was used and the survey was used as an instrument, which was a Likert-style questionnaire composed of 18 items. It was concluded that, when correlating the variables through the Spearman’s Rho correlation, a value of 0.872 resulted, indicating that there is a high positive level between the strategic strengthening of citizenship and common crime, a result that confirms that citizen participation It is essential for positive relationships between public and / or private institutions with citizens, in order to carry out comprehensive actions to eradicate and / or reduce common crime in the Santiago de Surco district. From the study of hypothesis contrast between the variables, an asymptotic significance value of 2.3% was obtained for a significance level of 5%, as the value obtained was lower with the critical value according to the significance level, which led to to affirm that the strategic strengthening of citizen participation allows the reduction of common crime